Asian women and intimate work (The intimate and the public in Asian and global perspectives, 2014)
"Asian women are often labelled with biased stereotypical images, ranging from "subordinate housewife" to "migrant domestic maid," and "overseas bride." Asian women, in fact, are being constructed as "women among women." These feminine roles are related to the various activities that women perform for others in intimate relationships both within and outside the family. This book comprises contributions from a distinguished group of international researchers who examine the historical development of "new women" and "good wife, wise mother," women's roles in socialist and transitional modernity and the transnational migration of domestic and sex workers as well as wives".